Evidence-based policy making? The case of Polish opposition to the EU Tobacco Products Directive - Zatoński, Mateusz (Journal of Health Inequalities, 2016)
In December 2012 the European Union (EU) Commission announced that it will propose a revision of the 2001 Tobacco Products Directive (TPD). This paper traces the policy debate that followed, in order to highlight some of the intricacies of the research-policy nexus. It focuses on the voting decisions of the Polish Members of the European Parliament (MEPs) during the European Parliament vote on the TPD in October 2013. The presented analysis employs a variety of theoretical models, including the engineering, enlightenment and strategic models of evidence-based policy making, the “two communities” model, framing, as well as Black’s list of reasons for why research evidence has little influence on service policies. The analysis demonstrates that a linear model of relation between research and policy is of little value in understanding the EU TPD voting outcomes due to the broad and strongly antagonistic nature of the advocacy coalitions competing to influence the political decisions of the MEPs on this issue.